"The Scallop Shells Carried by Pilgrims" - Medicinal Use by Peter of Spain - do Sameiro Barroso, Maria (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
Petrus Hispanus, also known as Peter of Spain (c. 1210-1277 CE), was a Portuguese physician who later became Pope John XXI. In his work Thesaurus Pauperum (Treasure of the Poor), which was one of the most popular books during the Middle Ages, he mentioned that "scallop shells carried by the pilgrims" could be used to manage menstrual overflow. He adapted this recipe from the Arabic physician Avicenna (c. 980–1037 CE). Interestingly, this leads us to consider the medicinal use of coral as well. Current scientific knowledge indicates that scallop shells are primarily composed of calcium carbonate, which can influence blood clotting. Additionally, the concave shape of scallop shells, which helped pilgrims drink during their journeys, evolved into a powerful symbol of their spiritual quest. Beyond their chemical properties, scallop shells represented aspects of spiritual well-being and beneficial healing forces, adding significant cultural meaning to their practical use.
Keywords: Saint James Way; Scallop shells; Peter of Spain; Coral; Calcium carbonate